Followers' Perception of Leadership Style, Organizational Commitment and Regulatory Focus, Moderated by Organizational Types - Mash, Roni; Cohen, Lihi (Asian Journal of Social Sciences and Management Studies, 2018)
Research hypotheses assumed that a positive connection would be found between transformational leadership, on one hand, and affective commitment and focus on promotion, on the other. It was also assumed that this connection would be stronger in coercive organizations. Furthermore, the research hypotheses assumed there would be positive connections between transactional leadership, on one hand, and continuance commitment and focus on prevention, on the other; stronger in utilitarian organizations. 82 employees of coercive organizations and 80 employees of utilitarian organizations participated in this study using the MLQ questionnaire, an organizational commitment questionnaire, and a regulatory focus questionnaire. It was found that the more a leader is perceived by followers as having a transformational style, the more followers will feel affective commitment toward the organization and the more they will focus on promotion and successes. Moreover, the more a leader is perceived as a transactional leader followers will feel more continuance commitment and be more focused on preventing failures. The moderation model by type of organization was confirmed. Difference between the connections noted above in coercive organizations as compared to utilitarian organizations was found.